Study Karaj River And Currents torrential It And its role in groundwater shahriar Plain - Parviz kardavani; Farideh Asadian; mohammad reza Fallah (تحقیقات کاربردی علوم جغرافیایی)
Indiscriminate exploitation of underground aquifers shahriar Plain loss of ground water in the region has created. Water penetration can increase the volume of groundwater reservoir and reduce the loss of it. One way of artificial recharge of aquifers, infiltration of water from riverbeds or running water. In this study, we have tried By examining the characteristics of Karaj River and its flood flows, parameters infiltration GIS examined, For this purpose, The different factors affecting this environment GIS to prepare maps of each factor was prepared. Then using acquired the weight of each layer map by weighted factors to locate the combine And using Boolean logic final map in two classes and is not appropriate was prepared. by matching the map obtained with the river Karaj identified were Due to Construction Dam Amir Kabir And the supply of drinking water in Tehran harvest Abundant by pools traditional and modern Drbaladst Karaj River, Karaj River with flood flows its role Lower in improving groundwater Shahriar Plain is capable.